The Conceptual Framework on Formation of Urban Heat Island in Tehran Metropolitan, Iran : A Focus on Urbanization Factor - Nurakmal, Abdullah@ Goh Tuo Ho; Khairul Nizam, Abdul Maulud; Che-Ani, A. I.; Mazlan, Mohd Tahir; Shahmohamadi, P.; Muhammad, Nor (2010)
In an urban area, one of the great problems is urban heat island effect, which is due to many factors such as urbanization and climatic factors, resulting from the production and accumulation of heat in the urban mass. The main characteristics of UHI effect are the raised temperatures in the city centre, leading to excessive energy use for cooling and putting urban population at great morbidity and mortality risks. Therefore, it becomes increasingly important to study that how could various factors form UHI over the city in order to reduce environmental challenges. This paper, therefore, is focused on urbanization and climatic factors to understand the influence way of these factors on formation of UHI. The percentage of UHI formation is high when great interaction exists. This paper explores literally the conceptual framework of interaction between urbanization and climatic factors on formation of UHI with the case study of city of Tehran. The urbanization factors that affect Tehran are discussed in relation to location of the city, the size of the city and population, density of built-up area, urban geometry, thermal property of fabric, surface waterproofing, anthropogenic heat, air pollution, land use and wind speed.